A new look at technical progress and early retirement - Lorenzo Burlon; Montserrat Vilalta-Bufí (IZA Journal of Labor Policy, 2016)
Technical progress affects early retirement in two opposing ways. On the one hand, it increases real wages and thus produces an incentive to postpone retirement. On the other hand, it erodes workers' skills, making early retirement more likely. We re-examine the effect of technical progress on early retirement in the US. We measure technical change during the whole working life of the individuals and find that its effect on the probability of early retirement is non-monotonic. In particular, when technical change is small, the erosion effect dominates, but when it is large the wage effect dominates. These results may signal that the higher the technical change, the more willing are the elderly to retrain, which has direct policy implications for the design of elderly training programs
Keywords: J24; J26; O33; 330; Early retirement; Technical change; Training